Terrain instability in the Tijuana metropolitan area: Analysis of a failure in the access road to a industrial park. (October 2019) - Oliva González, Aldo O.; Berumen Rodríguez, Marco A.; Gallardo Amaya, Romel J.; Jaramillo, Haidee Yulady
Abstract: This article analyzes the main causes of terrain instability in the urban area of the Tijuana city, Mexico, and describes its main conditioning and triggering factors. We present the case of a fault that occurred in the access road of an industrial park and the study carried out to investigate its causes, which included two stages: in the first, the main pathologies in the fault zone were identified, a terrain geotechnical characterization was made, and hypotheses were analyzed about the probable mechanism of the failure; and in the second, the analysis of the terrain stability and deformability was carried out by means of computer simulations that allowed to evaluate the influence of different conditioning and triggering factors of the event. The analysis of the causes of the terrain instability and the study of the presented case, allowed to issue conclusions on the natural and anthropic factors that most influence the occurrence of faults, and to give recommendations related to the design and construction of roads in urban areas. Highlights: The main causes of terrain instability in the urban area of Tijuana are analyzed. The main conditioning and triggering factors of instability are described. The case study of a fault occurred in the access road to a industrial park is presented.